2014
DOI: 10.5860/crl12-372
|View full text |Cite
|
Sign up to set email alerts
|

Publication and Language Trends of References in Spanish and Latin American Literature

Abstract: This study examined references found in three journals in the field of Spanish and Latin American literary studies. Few previous studies have examined types of publishers producing highly cited/referenced books. The data indicate that the primary publishers of scholarly monographs referenced in the journals are U.S. university presses, foreign academic trade presses, and foreign popular trade presses. U.S. university presses, foreign academic trade presses, and government entities published most of the volumes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…We found that the proportion of foreign-language references in an article also associated with citation counts. A study of the usage of English-language resources by Spanish and Latin American literature scholars shed light on the percentage growth of foreign resources in humanities (Nolen 2014).…”
Section: Reference-related Factorsmentioning
confidence: 99%
“…We found that the proportion of foreign-language references in an article also associated with citation counts. A study of the usage of English-language resources by Spanish and Latin American literature scholars shed light on the percentage growth of foreign resources in humanities (Nolen 2014).…”
Section: Reference-related Factorsmentioning
confidence: 99%
“…A study by David Nolen (2014) found that, in a single year, nearly 38 % of all references to scholarly monographs in three top Latin American Literary Studies journals were to foreign university, academic, and governmental publications. This suggests that there may be a motivation for research libraries to enhance discovery of and access to the OA book production from these types of publishers.…”
Section: Developing a Web Portal For Latinmentioning
confidence: 99%
“…12 Similarly, in his analysis of three journals in the field of Spanish and Latin American literature, Nolen concludes that scholarly monographs and volumes of collected essays are highly referenced materials growing in importance over the years between 1970 and 2000. 13 Mendez and Chapman discussed the use of citations in the Hispanic American Historical Review and concluded that English language materials represent about twothirds of all citations. 14 Schadl and Todeschini examined dissertations across academic departments and showed that English language materials predominated, representing 85 percent of all citations.…”
mentioning
confidence: 99%